Atopy manifestations in pediatric patients with acute lymphoblastic leukemia: correlation assessment with interleukin-4 (IL-4) and IgE level - Omid Reza Zekavat; Elham Nikpendar; Sezaneh Haghpanah; Negin Shokrgozar; Seyed Javad Dehghani; Nargess Arandi (BMC Pediatrics, 2022)
Abstract Background Acute lymphoblastic leukemia (ALL) is the most common type of cancer in the age range of under 15 years old and accounts for 25–30% of all childhood cancers. Although conventional chemotherapy regimens are used to improve the overall survival rate, it has been associated with some complications, amongst which allergic manifestations with unknown mechanisms are more common. Methods Our study compared serum IgE and IL-4 concentration, as a hallmark of allergic responses in pediatric ALL patients before and after 6 months of intensive (high-dose) chemotherapy, to show whether changes in the level of these markers may be associated with atopy. Serum level of IL-4 and IgE was measured using enzyme-linked immunosorbent assay (ELISA) method. Results The results showed that the level of IgE and IL-4 increased following chemotherapy in both ALL patients with and without atopy. In addition, post-chemotherapy treatment IgE and IL-4 levels were significantly elevated in patients with atopy compared to those without it. The difference between baseline and post-chemotherapy level of IgE and IL-4 was significantly higher in patients with atopy compared to those without it. Conclusions To the best of our knowledge, this is the first study that showed a connection between post-chemotherapy allergic manifestations in pediatric ALL patients and IL-4 and IgE level. Flow cytometry analysis of the T-helper 2 (Th2) lymphocytes and other allergy-related T cell subsets like Tc2 and Th9 as well as the study of the genetic variations in atopy-related genes like IL-4/IL-4R, IL-5, IL-9, IL-13, and high affinity FcεRI IgE receptor and also HLA genes is necessary to clearly define the underlying mechanism responsible for post-chemotherapy hypersensitivity reaction in pediatric ALL patients.